A farewell from the editor to Interlending and Document Supply. Issue 4 (21st November 2016) - McGrath, Mike
Abstract : Purpose: This study aims to reflect on developments in document supply and scholarly communications and to look into the future of the service. Design/methodology/approach: This study provides an informal overview. Findings: The results of this study indicate that Interlending and Document Supply ( ILDS ) as a service has a long future ahead of it albeit at a lower level than in the recent past. Originality/value: As a farewell to ILDS, it is inevitably original; its value will be judged by the reader.